RANCANG BANGUN SISTEM PENGADUAN LAYANAN AKADEMIK STMIK STIKOM INDONESIA - suryawan, I Gede Totok; Handika, I Putu Susila (SINTECH (Science and Information Technology) Journal, 2018)
This paper discusses the design of academic service complaints system in STMIK STIKOM Indonesia. Currently, the evaluation of academic services at STMIK STIKOM Indonesia has been done periodically in the form of distributing questionnaires to the students before taking the final exam of Semester (UAS) in each semester. This evaluation is quite effective but this periodic evaluation can not yet accommodate the academic service complaints that occur in the everyday incident. In this paper has developed a system of web-based academic service complaints that can be accessed at any time by the academic community to provide feedback related to academic services at STMIK STIKOM Indonesia. In general, the system is capable of managing user data such as students, lecturers, institutions, and administrators. The system is able to make a complaint file to be sent to service provider units within the academic community, and the files sent will be accessed through the "outbreak" menu whereas in the complaint recipient account it can be accessed in the "incoming complaint" menu. To maintain the security of the complaints process on the system also facilitates the user to encrypt and decrypt the complaint file. Based on the tests that have been done the system developed able to facilitate students and academic community in general to conduct complaints of academic services and teaching and learning facilities at STMIK STIKOM Indonesia. Security of complaint data can be maintained well with the existence of encryption facilities and description and distribution of keys made directly to each user. From the test conducted by testing the functions expected in the system, obtained the results that the system is able to run in accordance with the expected.